2014
DOI: 10.1038/ki.2013.286
|View full text |Cite
|
Sign up to set email alerts
|

TNF-mediated damage to glomerular endothelium is an important determinant of acute kidney injury in sepsis

Abstract: Severe sepsis is often accompanied by acute kidney injury (AKI) and albuminuria. Here we studied whether the AKI and albuminuria associated with lipopolysaccharide (LPS) treatment in mice reflects impairment of the glomerular endothelium with its associated endothelial surface layer. LPS treatment decreased the abundance of endothelial surface layer heparan sulfate proteoglycans and sialic acid, and led to albuminuria likely reflecting altered glomerular filtration perm-selectivity. LPS treatment decreased the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
142
7
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(159 citation statements)
references
References 68 publications
7
142
7
3
Order By: Relevance
“…42 Extrarenal TLR4 and increased TNF-a are associated with increased BUN and the progression of kidney damage after LPS injection in mice. [43][44][45] By contrast, we found no evidence that TNF-a contributes to the LPS-induced reduction in tubular flow rate. This discrepancy may result from differences in experimental settings, such as mouse age and strain, as well as LPS dosage.…”
Section: Discussioncontrasting
confidence: 47%
“…42 Extrarenal TLR4 and increased TNF-a are associated with increased BUN and the progression of kidney damage after LPS injection in mice. [43][44][45] By contrast, we found no evidence that TNF-a contributes to the LPS-induced reduction in tubular flow rate. This discrepancy may result from differences in experimental settings, such as mouse age and strain, as well as LPS dosage.…”
Section: Discussioncontrasting
confidence: 47%
“…TNF-␣ has been shown, through its TNF receptor on renal endothelial cells, to cause acute kidney injury and structural changes in glomerular endothelial cells 24 h after the TNF-␣ injection. Alterations in the endothelial surface layer composition and decreased fenestral density, with enlargement of fenestral diameters and loss of fenestrae, have been demonstrated, with no major changes in podocyte morphology (58). Furthermore ROS infusion per se has been shown to cause dose-dependent transient proteinuria without ultrastructural abnormalities (60).…”
Section: Stokes-einstein Radius (å)mentioning
confidence: 99%
“…Studies of TNF-␣ action on isolated glomeruli in vitro have demonstrated an increased permeability of the glomerular filtration barrier (GFB) to albumin (at 15 min), mediated via the generation of reactive oxygen species (ROS) (36). Bertani et al (11) studied the effects of intravenous TNF-␣ infusion (0.8 -8 g·kg Ϫ1 ·h Ϫ1 ) on glomerular function and structure and found a dose-dependent glomerular endothelial cell "injury," although they did not show increases in proteinuria after 15 or 24 h. Recently, it was suggested that TNF-␣ (at a plasma concentration of 6.7 Ϯ 1.3 ng/ml) may mediate much of the actions of (bacterial) LPS on the glomerular endothelium and that TNF-␣ in mice can induce similar alterations as LPS when infused intravenously, contributing to an increased glomerular albumin permeability (58).…”
mentioning
confidence: 99%
“…33,34 In turn, inflammation is an important accelerator of tubular injury 15, 85 and involves potential triggers of necroptosis such as TNF-a. 86,87 Oxalate crystal formation inside tubules induces RIPK3-and MLKL-dependent tubular cell death (S.R. Mulay and H.-J.…”
Section: Sepsis Urosepsismentioning
confidence: 99%